2020
DOI: 10.1016/j.yebeh.2019.106520
|View full text |Cite
|
Sign up to set email alerts
|

Acute symptomatic seizures and epilepsy after mechanical thrombectomy

Abstract: To assess the incidence of acute symptomatic seizures and post-stroke epilepsy (PSE) in a well-characterized cohort of patients treated with mechanical thrombectomy. In addition, we aimed to describe the dynamics of blood markers of brain injury in patients that developed PSE. Methods: Participants of the prospective AnStroke Trial of anesthesia method during mechanical thrombectomy were included and acute symptomatic seizures and PSE ascertained by medical records review. Blood markers NFL, tau, GFAP, S100B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
1
18
2
Order By: Relevance
“…In line with literature, the prevalence of stroke‐related epilepsy was almost 6%, and it occurred more often in patients with higher NIHSS scores and a history of early onset seizures 6,2 . Approximately 7% of the patients who underwent reperfusion treatment developed poststroke epilepsy, similar to earlier studies in which incidence ranged between 4% and 16.7% 15,20,21 . In our study, because cortical involvement was strongly associated with stroke severity (NIHSS), no significant results were found after performing a multiple regression analysis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with literature, the prevalence of stroke‐related epilepsy was almost 6%, and it occurred more often in patients with higher NIHSS scores and a history of early onset seizures 6,2 . Approximately 7% of the patients who underwent reperfusion treatment developed poststroke epilepsy, similar to earlier studies in which incidence ranged between 4% and 16.7% 15,20,21 . In our study, because cortical involvement was strongly associated with stroke severity (NIHSS), no significant results were found after performing a multiple regression analysis.…”
Section: Discussionsupporting
confidence: 89%
“…6,2 Approximately 7% of the patients who underwent reperfusion treatment developed poststroke epilepsy, similar to earlier studies in which incidence ranged between 4% and 16.7%. 15,20,21 In our study, because cortical involvement was strongly associated with stroke severity (NIHSS), no significant results were found after performing a multiple regression analysis. Of note, mortality rate was up to 41% in accordance with long-term mortality studies that reported mortality rates up to 72%; 22 thus, our mortality rate is that expected in the long term.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In addition, the vast majority of these studies only investigated IVT therapy, reporting a risk for acute symptomatic seizures after rt-PA treatment between 1-4%. Only a few studies have investigated the effect of MT on the frequency of acute symptomatic seizures 23,[31][32][33] .…”
Section: Scientific Reportsmentioning
confidence: 99%
“…With a sensitivity of predicting poststroke epilepsy being 100%, the best specificity can still reach 77%~93%. However, given the low incidence of poststroke epilepsy in this study, statistical analysis was not further performed [63]. Recent meta-analyses of several cohorts provide a multitude of evidence that support the elevation of S100B protein level in epilepsy patients.…”
Section: Neuroprotein Biomarkersmentioning
confidence: 95%